2020
DOI: 10.1111/ejh.13500
|View full text |Cite
|
Sign up to set email alerts
|

Febrile neutropenia in patients with acute myeloid leukemia: Outcome in relation to qSOFA score, C‐reactive protein, and blood culture findings

Abstract: Objectives: To evaluate quick Sequential Organ Failure Assessment (qSOFA) score during febrile neutropenia (FN) in adult patients receiving intensive chemotherapy for acute myeloid leukemia (AML). Methods: qSOFA score, as well as the association of qSOFA score with ICU admission, infectious mortality, blood culture findings, and C-reactive protein (CRP) measurements during FN were assessed among 125 adult AML patients with 355 FN periods receiving intensive chemotherapy in a tertiary care hospital from Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
2
1
Order By: Relevance
“…Age, multidrug resistant (MDR) organism, time to chemotherapy initiation, and comorbidities have variable effect on mortality in AML induction. 20,[36][37][38] In our study, on the univariate analyses, age, sex, symptoms duration, performance status, comorbidity, blood culture positivity, or organ localization had no significant effect on outcome. Days to develop FN were inversely associated with OS, though there was no statistically significant difference in OS.…”
Section: Discussioncontrasting
confidence: 49%
“…Age, multidrug resistant (MDR) organism, time to chemotherapy initiation, and comorbidities have variable effect on mortality in AML induction. 20,[36][37][38] In our study, on the univariate analyses, age, sex, symptoms duration, performance status, comorbidity, blood culture positivity, or organ localization had no significant effect on outcome. Days to develop FN were inversely associated with OS, though there was no statistically significant difference in OS.…”
Section: Discussioncontrasting
confidence: 49%
“…Despite this, we found that a qSOFA score ≥ 2 was independently associated with ICU mortality. In a study that analyzed AML patients with febrile neutropenia, a qSOFA score ≥ 2 was also associated with infectious mortality and was a good predictor of mortality when combined with C-reactive protein [21]. A study of cancer patients that included 23.4% of patients with hematological malignancies found that a qSOFA score ≥ 2 is associated with higher risk of hospital mortality and a prolonged ICU stay [22].…”
Section: Discussionmentioning
confidence: 99%
“…The qSOFA score is based in 3 simple variables, which include respiratory rate ≥22/min, alteration in mental status, and systolic blood pressure ≤100 mm Hg (96). The SOFA and qSOFA scores are therefore useful tools to identify and predict complications and mortality in these patients (97)(98)(99), and as such, should be applied to all cancer patients with suspected infection.…”
Section: Optimal Management Of Sepsis In Cancer Patients Early Recognmentioning
confidence: 99%